The Transformational Leadership Style for Further Psychological Improve on Personnel Emergency Health Room at Siloam Kebun Jeruk Hospital, Jakarta - Helvyda Sari; W. Dian Purwanti; Rina Anindita (Journal of Multidisciplinary Academic, 2021)
During the Covid-19 pandemic, health workers experienced fatigue both physically and mentally. The emergency room (ER) is a unit that requires fast and correct handling, Here, the level of stress experienced by health workers in the ER, especially during the Covid-19 pandemic was increased. The psychological of health workers is influenced by many things, including transformational leadership style, work environment, and community stigma. Thus, in study we analyze the influence of transformational leadership style, work environment, and community stigma on the pyschogical of emergency room health workers at Siloam Kebun Jeruk Hospital during the Covid-19 pandemic, (partially or simultaneously). in this study uses a mixed method research method that combines qualitative and quantitative research methods. The result that transformational leadership style has a significant positive effect on the psychology of health workers, the work environment has no effect on the psychological of health workers, the stigma of society has no effect on the psychological of health workers. Transformational leadership style, work environment, and community stigma together influence the psychological of health workers. The implication of this study that leader of the ER is advised to listen to the ideas, motivation, leadership in a meeting or briefing. Here, a conducive work environment at Kebun Jeruk Siloam Hospital can improve the psychological level of emergency room health workers. The stigma of society is negative for the psychology of health workers due to dedication and professional value of workers. Their commitment to health services has not wavered even during the pandemic, but the hospital strives for psychological safety for health workers with other factors.